(untitled) (Journal of Information Technologies in Education (ITE), 2015)
In publishing the proposed method, which aims at the formation of professional knowledge and skills students software engineers. Established that additional tools positive impact on the learning process while teaching raises interest in the subject and the profession in general, as it allows embroidered minded students. Identified in the course of implementation developed by the author of the product, it fits well in today’s learning environment and is a good helper, not only students but also teachers. Based on the analysis it was found positive and negative aspects of the application of modern techniques in a learning environment. We describe the structure of the phases and possible applications in the educational process designed educational computer program.Determined that the formation of professional knowledge and skills students need to use as many contemporary visual arsenal.